\(\frac{x-4}{x-4\sqrt{x}+4}\)-\(\frac{x+2\sqrt{x}}{x-...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 6 2018

mik chịu

11 tháng 7 2017

a, \(P=\frac{x-4}{\sqrt{x}\left(\sqrt{x-2}\right)}.\frac{\sqrt{x}+2}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-2\right)}\)

\(=\frac{\left(\sqrt{x}+2\right)\left(\sqrt{x}-2\right)}{\sqrt{x}\left(\sqrt{x}-2\right)}.\frac{\sqrt{x}+2}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-2\right)}=\frac{\sqrt{x}+2}{x-2\sqrt{x}}\)

b. Với \(x=4+2\sqrt{3}\Rightarrow P=\frac{\sqrt{4+2\sqrt{3}}+2}{4+2\sqrt{3}-2\sqrt{4+2\sqrt{3}}}\)

\(=\frac{\sqrt{3}+1+2}{4+2\sqrt{3}-2\left(\sqrt{3}+1\right)}=\frac{3+\sqrt{3}}{2}\)

C. \(P>0\Rightarrow\frac{\sqrt{x}+2}{x-2\sqrt{x}}>0\Rightarrow x-2\sqrt{x}>0\Rightarrow x>4\)

luyện thi học kì 1 

23 tháng 8 2019

\(\frac{x+2+\sqrt{x^2-4}}{x+2-\sqrt{x^2-4}}+\frac{x+2-\sqrt{x^2-4}}{x+2+\sqrt{x^2-4}}\)

\(=\frac{\left(x+2+\sqrt{x^2-4}\right)^2+\left(x+2-\sqrt{x^2-4}\right)^2}{\left(x+2+\sqrt{x^2-4}\right)\left(x+2-\sqrt{x^2-4}\right)}\)

\(=\frac{\left(x^2+4+x^2-4+4x+2\sqrt{x^2-4}+x\sqrt{x^2-4}\right)+\left(x^2+4+x^2-4+4x-2\sqrt{x^2-4}-x\sqrt{x^2-4}\right)}{x^2+2x-x\sqrt{x^2-4}+2x+4-2\sqrt{x^2-4}+x\sqrt{x^2-4}+2\sqrt{x^2-4}-x^2+4}\)\(=\frac{4x^2+8x}{4x+8}=\frac{4x\left(x+2\right)}{4\left(x+2\right)}=x\)

23 tháng 8 2019

\(DK:x\ne1,-1,-2\)

\(\frac{x+2+\sqrt{x^2-4}}{x+2-\sqrt{x^2-4}}+\frac{x+2-\sqrt{x^2-4}}{x+2+\sqrt{x^2-4}}\)

\(=\frac{\left(x+2+\sqrt{x^2-4}\right)^2+\left(x+2-\sqrt{x^2-4}\right)}{\left(x+2\right)^2-x^2+4}\)

\(=\frac{\left(x+2\right)^2+2\left(x+2\right)\sqrt{x^2-4}+x^2-4+\left(x+2\right)^2-2\left(x+2\right)\sqrt{x^2-4}+x^2-4}{4x+8}\)

\(=\frac{4x^2+8x-8}{4x+8}\)

\(=\frac{x^2+2x-2}{x+2}\)